Strategi Pengembangan Sumber Daya Manusia di Era Digital pada Perguruan Tinggi Keagamaan Islam: Studi Kasus Pada IAI Pangeran Dharma Kusuma Indramayu - Casriyanti Casriyanti (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
This study aims to analyze human resource development strategies in the digital era at the Institut Agama Islam Pangeran Dharma Kusuma Indramayu. The digital era requires higher education institutions to have adaptive and innovative human resources in technology and teaching. This qualitative descriptive research employed interviews, observations, and documentation. The findings show that HR development strategies were implemented through digital literacy training, administrative digitalization, and faculty competence improvement. The main challenges were limited technological infrastructure and resistance to change. Continuous training, mentoring, and managerial policy support were applied as solutions. The study concludes that successful HR development in the digital era requires synergy and commitment across all organizational elements.